Pengaruh Senam Otak Terhadap Koordinasi Antara Mata dan Tangan Anak-Anak TK Al-Firdaus Majalengka - Widyawati, Yulan, Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes, Dwi Rosella K, S.Fis.,Ftr.,M.Fis (2015)
Background: When children are growing, more motoric skills are acquired in order to grow and develop optimally. Coordination of eyes and hands is a fine motoric skill that is necessary not only in academic area, but to acquire self-reliance and social acceptability to avoid poor personality shaping and adjustment. Purpose: purpose of the research is to know effect of brain gym on eyes and hands coordination among childrens of Al-Firdaus Kindergarten. Method: The research is a quasi-experimental one with pre and post test approach of a group with treatment of brain gym and a control group. Twenty one respondents of 5-6 years old are included in the treatment group and 19 respondents with similar ages are included in the control group. Independent variable of the research is brain gym and dependent variable is eyes and hands coordination. Data analysis of the research used wilcoxon sign rank and mann whitney test. Results: Data analysis of wilcoxon sign rank obtained p value = 0.02, p = 0.000, p = 0.046, p = 0.000 indicating that an improvement in every sub test was found. While, analysis of mann whitney test obtained p value = 0.02, p = 0.000, p = 0.0021, p = 0.002 meaning that different effect was found between treatment group and control group. Conclusion: Brain gym has effect on eyes and hands coordination of childrens of Al-Firdaus Kindergarten Majalengka.